Quality assessment of elderberry (Sambucus nigra L.) jams - Oana-Viorela Nistor; Doina-Georgeta Andronoiu; Liliana Ceclu (Czech Journal of Food Sciences)
Elderberries belong to the spontaneous flora of Sambucus nigra L., being considered wild fruits and even improper to be consumed. Dark violet-black and slightly glossy elderberry fruits are rich in bioactive compounds such as agglutinin, total anthocyanins and polyphenols. The importance of heating is claimed by the seasonal and toxic specific elderberry fruits. Moreover, the need to transform the fruits from not suitable for consumption into functional products and to prolong the shelf life of the product should be highlighted. Based on these affirmations, the aim of the study was to preserve the elderberries as jam with or without refined sugar. Phytochemical, textural, colour and sensory analyses were used to characterize three samples of jams (one without sugar, one with refined sugar and one with stevia sugar). The samples with stevia sweetener addition showed the highest values of anthocyanins (1.43 ± 0.16 mg.g-1 dry matter, DM) among the processed samples; as for the raw fruits, the anthocyanin content showed a decrease. The antioxidant activity determined by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay revealed similar values between all the analysed elderberry jams. In accordance with the other results, the most appreciated sample by the sensory evaluation was the sample with stevia sweetener. As a conclusion, the total sugar substitution could contribute to a more valuable matrix than the original one. The novelty of the study consists in the use of such popular spontaneous flora of Sambucus nigra L. berries and in a change of the inedible character of the raw fruits into edible functional foods with a prolonged shelf-life.